Bamboo for Beverage Containers of Legen and Tuak as a Reflection of Local Wisdom of Tuban Society - Listia Natadjaja; Elisabeth Christine Yuwono (Jurnal Desain Komunikasi Visual Nirmana, 2023)
Legen and tuak beverage container made of bamboo has different names and functions namely bethek, centhak and ongkek. This study aims to see how people use bamboo as part of local wisdom in the form of legen and tuak container. The society gaining knowledge from living with the nature finds that the functions of a bamboo are being thermal insulation, being a not-easily-broken container, maintaining flavor and aroma, and making the content in it more durable. Apparently, the sustainability of this natural-made packaging is not only due to its function which is tangible but also related to the socio-cultural of the local community especially how they produce, consume and distribute legen and tuak.  In practice, local wisdom of bamboo as legen and tuak beverage containers continuously gives attention to the balance of nature that does not destroy or force the nature to produce more than its capacity, it is inherited from generation to generation, and it is correlated to the culture. It contains the philosophy of self-controlled and sharing.